2019
DOI: 10.5535/arm.2019.43.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Issues in Cerebral Palsy Associated With Aging: A Physiatrist Perspective

Abstract: The population of adults diagnosed with cerebral palsy (CP) is increasing along with the survival rate of children born with the disability. Adults with CP need health services for the continued monitoring and management of their condition. Moreover, the development of additional health problems in adulthood increases the need for ongoing access to health services. Adults with CP manifest a higher rate of chronic health conditions and eventual decline in strength and functional reserve, deterioration in physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 71 publications
(104 reference statements)
0
23
0
Order By: Relevance
“…Consequently, a nervous-system-independent, safe, and effective treatment is a significant unmet need from both clinical and socio-economical perspectives. Therefore, MPH-220 is a promising anti-spastic drug candidate to improve quality of life and may contribute to extended life expectancy (Blair et al, 2019;Gillard et al, 2015;Slaman et al, 2014;Yi et al, 2019) of these patients and would provide new therapeutic protocols for clinicians in these diverse indications.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a nervous-system-independent, safe, and effective treatment is a significant unmet need from both clinical and socio-economical perspectives. Therefore, MPH-220 is a promising anti-spastic drug candidate to improve quality of life and may contribute to extended life expectancy (Blair et al, 2019;Gillard et al, 2015;Slaman et al, 2014;Yi et al, 2019) of these patients and would provide new therapeutic protocols for clinicians in these diverse indications.…”
Section: Discussionmentioning
confidence: 99%
“…For youth with CP, the loss of pediatric health care and school-based support systems presents enormous challenges. A lack of strong societal support mechanisms is well-documented for people with disabilities and leads many young adults with CP to struggle with independence, higher education, and employment ( 2 , 5 11 , 30 ). These observations have been documented in other countries, such as Norway where individuals with CP had lower odds of completing upper secondary education and had higher odds of receiving a disability pension ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that adults with CP face declining health with aging related to increased levels of pain ( 2 , 30 , 33 , 34 ). For instance, a study on self-reported health outcomes found that 63% of adults with CP report chronic pain ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations